2020
DOI: 10.3390/ijms21176415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seminal Plasma Protein Fractions on Stallion Sperm Cryopreservation

Abstract: Seminal plasma (SP) is the natural environment for spermatozoa and contains a number of components, especially proteins important for successful sperm maturation and fertilization. Nevertheless, in standard frozen stallion insemination doses production, SP is completely removed and is replaced by a semen extender. In the present study, we analyzed the effects of the selected seminal plasma protein groups that might play an important role in reducing the detrimental effects on spermatozoa during the cryopreserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
(128 reference statements)
1
11
0
Order By: Relevance
“…In the case of the fraction containing 50-100 kDa proteins, the effects were less clear, as the viability of bound-to-PMN sperm population was lower than both the control and the fraction containing 30-50 kDa proteins after 2 h and 3 h of incubation at 38 • C. Remarkably, viability of the unbound sperm population was the lowest in fractions containing small proteins (< 3 kDa and 3-10 kDa). Related to this, when they remain in contact with spermatozoa, low molecular proteins (i.e., <10 kDa) are not beneficial for sperm, but rather they reduce motility and damage plasma membrane integrity in several species [35][36][37][38][39]. The effect of these proteins could explain why the addition of seminal plasma semen does not improve frozen-thawed donkey sperm [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the fraction containing 50-100 kDa proteins, the effects were less clear, as the viability of bound-to-PMN sperm population was lower than both the control and the fraction containing 30-50 kDa proteins after 2 h and 3 h of incubation at 38 • C. Remarkably, viability of the unbound sperm population was the lowest in fractions containing small proteins (< 3 kDa and 3-10 kDa). Related to this, when they remain in contact with spermatozoa, low molecular proteins (i.e., <10 kDa) are not beneficial for sperm, but rather they reduce motility and damage plasma membrane integrity in several species [35][36][37][38][39]. The effect of these proteins could explain why the addition of seminal plasma semen does not improve frozen-thawed donkey sperm [5].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the insemination dose, a single Kacang goat ejaculate could be divided into 57 doses (0.38 mL volume) with 12 μ g IGF-I complex protein/mL SM-EY extender (T1). Bubenickova et al [ 55 ] reported a positive correlation between the concentration of IGF-I complex protein in horse seminal plasma and the concentration, morphology, and motility of sperm. In addition, IGF-I maintained ram sperm functions following chilled storage [ 56 ] by providing a stable energy supply for sperm metabolism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa motility was higher in sperm samples with a high concentration of seminal IGF-1, and higher concentrations of IGF-1 are associated with higher sperm motility [45]. In addition, the concentration of the IGF-1 complex protein in seminal plasma is positively correlated with the concentration, morphology, and motility of sperm [75]. However, in this study, a higher dose of IGF-1 (T2 group) showed higher motility and viability of Kacang buck semen than the T0 group, but sperm motility and viability of the T2 group were lower than those of the T1 group sperm (Table -2).…”
Section: )mentioning
confidence: 93%